Distinguishing Islam from cultural practices: Conversations with Qaisra Shahraz - Hasan, Md. Mahmudul (International Islamic University Malaysia, 2016)
South Asian writers both in diaspora and in the homeland are “currently experiencing an explosion of popular Anglophone forms” and are “being recognised by mainstream commercial publishers, and finding readers outside the traditional literary fiction market” (Chambers). In terms of the volume of writing being produced, and its critical reception, British writers of South Asian origin have already made an indelible mark on mainstream British literature. However, there is a caveat to the recognition of well-established writers from South Asia in Britain that other “equally great writers” of considerable artistic output may have been neglected (Chambers). Qaisra Shahraz (1958-) is one of those neglected writers whose greatness has not been adequately recognised and whose work has not received comparable critical attention. It is in this spirit that I introduce her and set forth the following reflections in order to delve deep enough into understanding the ramifications of her work.